Next-generation batteries and fuel cells for commercial, military, and space applications - Jha, A. R. (CRC Press, 2012)
"Next-generation batteries have higher power density and higher energy density and can be put into new forms with lower-cost mass production. This book focuses on technologically advanced secondary (rechargeable) batteries in both large and small format. It covers advanced technologies as replacements for NiCd and NiMH, especially advanced lithium-ion batteries that make use of new electrode materials and electrolytes. The author discusses printable batteries and thin-film battery stacks as enablers of micropower applications as well as hybrid battery/fuel cell systems, which are emerging as complements to consumer electronics batteries"--